Rcs phosphorelay affects the sensitivity of Escherichia coli to plantaricin BM-1 by regulating biofilm formation - Bian, Zheng; Liu, Wenbo; Jin, Junhua; Hao, Yanling; Jiang, Linshu; Xie, Yuanhong; Zhang, Hongxing (Frontiers in Microbiology, 2022)
Plantaricin BM-1 is a class IIa bacteriocin produced by Lactobacillus plantarum BM-1 that exerts significant antibacterial activity against many foodborne bacteria. Studies have shown that class IIa bacteriocins inhibit gram-positive bacteria via the mannose phosphotransferase system; however, their mechanism of action against gram-negative bacteria remains unknown. In this study, we explored the mechanism through which the Rcs phosphorelay affects the sensitivity of Escherichia coli K12 cells to plantaricin BM-1. The minimum inhibitory concentrations of plantaricin BM-1 against E. coli K12, E. coli JW5917 (rcsC mutant), E. coli JW2204 (rcsD mutant), and E. coli JW2205 (rcsB mutant) were 1.25, 0.59, 1.31 and 1.22 mg/mL, respectively. Growth curves showed that E. coli JW5917 sensitivity to plantaricin BM-1 increased to the same level as that of E. coli K12 after complementation. Meanwhile, scanning electron microscopy and transmission electron microscopy revealed that, under the action of plantaricin BM-1, the appearance of E. coli JW5917 cells did not significantly differ from that of E. coli K12 cells; however, cell contents were significantly reduced, and plasmolysis and shrinkage were observed at both ends. Crystal violet staining and laser scanning confocal microscopy showed that biofilm formation was significantly reduced after rcsC mutation, while proteomic analysis identified 382 upregulated and 260 downregulated proteins in E. coli JW5917. In particular, rcsC mutation was found to affect the expression of proteins related to biofilm formation, with growth curve assays showing that the deletion of these proteins increased E. coli sensitivity to plantaricin BM-1. Consequently, we speculated that the Rcs phosphorelay may regulate the sensitivity of E. coli to plantaricin BM-1 by affecting biofilm formation, thus providing new insights into the mechanism of class IIa bacteriocins against gram-negative bacteria.